IMPACT OF ETHNICALLY DIVERSE CEOS AND CONTEXT ON COMPANY PERFORMANCE. INSIGHTS FROM THE US TECH INDUSTRY. - Jain, Shreya (2020)
Existing literature on the Strategy and Leadership dialogue surrounds the debate on CEO succession and CEO background and characteristics. CEO succession theory and Upper Echelons theory are at the crux of this literature to understand key characteristics and strategic choices followed by the CEOs that ultimately influence company performance. The research integrates Resource Based View of the Firm theory, Glass Ceiling, Resource Dependency theory, Agency theory, Human Capital theory and Corporate Governance theory to acknowledge the role of resource availability, biases, board diversity and TMT stability on company performance. The aim of this research is to bridge the gap in existing literature by understanding the effects of ethnic diversity amongst the CEOs on company performance. By introducing narrative case studies on leading US technology firms, Microsoft, Google and Advanced Micro Devices, key findings are put forth qualitatively. It is evident that the company performance against the NASDAQ index is mixed in the presence of ethnically diverse CEOs. However, diverse CEOs positively influence the value of the company as measured by share price performance, through greater innovations and investments, increased workforce diversity and TMT stability. In supposition, the context under which a firm operates matters along with ethnic diversity amongst the CEOs.